A Randomized Controlled Trial of a Positive Family Holistic Health Intervention for Probationers in Hong Kong: A Mixed-Method Study - Lai, Agnes Y.-K.; Sit, Shirley M.-M.; Thomas, Carol; Cheung, George O.-C.; Wan, Alice; Chan, Sophia S.-C.; Lam, Tai-hing (Frontiers in Psychology, 2021)
Introduction: Probationers, offenders with less serious and non-violent offences and under statutory supervision, have low levels of self-esteem and physical health, and high level of family conflict, and poorer quality of family relationships. This study examined the effectiveness of the existing probation service and the additional use of a positive family holistic health intervention to enhance physical, psychological and family well-being in probationers and relationships with probation officers. Methods: Probationers under the care of the Hong Kong Social Welfare Department were randomized into a care-as-usual control group(CAU), a brief intervention group(BI) receiving two 1-hour individual sessions [of a brief theory-based positive family holistic health intervention integrating Zero-time Exercise(simple and easy-to-do lifestyle-integrated physical activity) and positive psychology themes of ‘Praise and Gratitude’ in the existing probation service], or a combined intervention group(CI) receiving BI and a 1-day group activity with family members. The outcomes were physical activity, fitness performance, self-esteem, happiness, anxiety and depression symptoms, life satisfaction, quality of life, family communication and well-being, and relationships with probation officers. Self-administered questionnaires and simple fitness tests were used at baseline, 1-month and 3-month follow-up. Linear mixed model analysis was used to compare differences in the changes of outcome variables among groups, adjusted of sex, age, and baseline values. Focus group interviews were conducted. Thematic content analysis was used. Results: 318 probationers (51% male) were randomized into CAU (n=105), BI (n=108) or CI (n=105) group. CAU showed enhanced physical activity, fitness performance and psychological health and family communication with small effect sizes(Cohen’s d=0.19-0.41). BI and CI showed further improved physical activity, family communication and family well-being(Cohen’s d=0.37-0.70). Additionally, CI reported greater improvements in the relationships with probation officers than CAU with a small effect size(Cohen’s d=0.43). CI also reported greater increases in physical activity and family communication than BI with small to moderate effect sizes(Cohen’s d=0.38-0.58). Qualitative feedbacks corroborated the quantitative findings. Conclusions: Our trial provided the first evidence of the effectiveness of probation service and the additional use of an innovative, relatively low-cost, theory-based brief positive family holistic health intervention. This intervention may offer a new model for enhancing probation service.